Exploring the options for the improvement of H2S adsorption on sludge derived adsorbents: Building the composite with porous carbons. (10th March 2020) - Florent, Marc; Policicchio, Alfonso; Niewiadomski, Szymon; Bandosz, Teresa J.
Abstract: With an objective to fully utilize a high catalytic capability of sludge-based adsorbents towards hydrogen sulfide oxidation, the composites consisting of a sewage sludge derived phase and coconut-carbon were synthesized with 10 and 30% of the latter phase. They were obtained by simple pyrolysis at 600, 800 and 950 °C. After an extensive surface characterization from the viewpoints of chemistry and porosity, their performance was tested in a hydrogen sulfide removal from a moist gas phase at ambient conditions. The results showed an improvement in the performance only for the samples obtained at 600 and 800 °C. These composites performed better than the hypothetical physical mixtures of the components and the highest hydrogen sulfide breakthrough capacity reached 22 mg/g, which was three times more than for only sludge derived samples. The improvement was linked to the availability of catalytic centers contributing to hydrogen sulfide oxidation and to an increase in the porosity from the carbon phase, where the products of reactive adsorption could be stored. On the other hand, pyrolysis of the composites at 950 °C decreased the performance in comparison with that of an only-sludge-based adsorbent (87 mg/g). It was linked to the high temperature effect of blocking the favorable chemistry of the sludge phase by the carbon particles and by blocking the pores of carbon by its sintering with the inorganic sludge-based phase. Graphical abstract: Image 1 Highlights: Sewage sludge/porous carbon composites were synthesized and used as H2 S adsorbents. An improved performance was found for the samples obtained at 600 and 800 °C. The improvement was linked to the catalytic centers and to an increase in porosity. Synthesizing composites at 950 °C had a detrimental effect on H2 S adsorption. The decreased performance was linked to deactivation of active centers by carbon phase.